Factors affecting the mechanical and geometrical properties of electrostatically flocked pure chitosan fiber scaffolds. Issue 17 (September 2018) - Tonndorf, Robert; Gossla, Elke; Kocaman, Recep Türkay; Kirsten, Martin; Hund, Rolf-Dieter; Hoffmann, Gerald; Aibibu, Dilbar; Gelinsky, Michael; Cherif, Chokri
The field of articular cartilage tissue engineering has developed rapidly, and chitosan has become a promising material for scaffold fabrication. For this paper, wet-spun biocompatible chitosan filament yarns were converted into short flock fibers and subsequently electrostatically flocked onto a chitosan substrate, resulting in a pure, highly open, porous, and biodegradable chitosan scaffold. Analyzing the wet-spinning of chitosan revealed its advantages and disadvantages with respect to the fabrication of the fiber-based chitosan scaffolds. The scaffolds were prepared using varying processing parameters and were analyzed in regards to their geometrical and mechanical properties. It was found that the pore sizes were adjustable between 65 and 310 µm, and the compressive strength was in the range 13–57 kPa.